Equilibrio trabajo-familia: corresponsabilidad familiar y autoeficacia parental en trabajadores de una empresa chilena (2013)
This article analyzes the differences between work-family balance, joint responsability and parental self-efficacy in employees of a Chilean company. 224 professional workers were administered three instruments: the work-family interaction questionnaire, the participation in family work questionnaire and the parental self-efficacy scale. It is observed that there is no difference in the level of work-family balance between men and women (t [222] = -0.83, p > 0,05). On joint responsibility, there are evident statistically differences (t [220,28] = -7,27, p < 0,05), indicating that women do more housework, despite their working day. Regarding parental self-efficacy, there are differences between men and women (t [215] = -8,76 p < 0,05), indicating that women perceive themselves as better mothers.Keywords: work-family balance, family joint responsibility, parental self-efficacy, family functioning.